An Analysis Of Figurative Language Used In Paulo Coelho's Adultery Novel (2014) - Wijayanti, Linda Ari, Dr. Anam Sutopo, M.Hum, Dr.Phil. Dewi Chandraningrum, M.Ed (2017)
This study focuses on analyzing the figurative language found in Paulo Coelho's Adultery novel. The aims of the study are to identify and describe the types of figurative language used in Adultery novel, to show the dominant type of figurative language used inAdultery novel, andto find the non-dominant type of figurative language used inAdultery novel. This study applies descriptive qualitative method. The data are figurative languages found in Adultery novel. The data sources are the novel entitled Adultery by Paulo Coelho in 2014 and the informants or raters or assessors. The method of collecting data is by using documentation. The findings of the study show that, firstly, there are four types of figurative languages used in Adultery novel, namely, comparison figurative language (simile, personification, metaphor, and allegory), opposition figurative language (hyperbole, antithesis, paradox, and apostrophe), linkage figurative language (metonymy, symbol, synecdoche, euphemism), and repetition figurative language (antanaclasis, chiasmus, and repetition). From 115 data, there are 56 or 48.6% data of comparison figurative language, there are 32 or 27.8% data of opposition figurative language, there are 8 or 7% data of linkage figurative language,there are 19 or 16.5% data of repetition figurative language includes. Secondly, the dominant type of figurative language is the comparison figurative language as many as 56 or 48.7% data from 115 or 100% data of figurative languages used in Adultery novel. Besides that, the most dominant figurative language used in Adultery novel is personification. Thirdly, the non-dominant type of figurative language used in Adultery novel is linkage figurative language as many as 8 or 7% data from 115 or 100% data of figurative languages. Besides that, the non-dominant figurative languages are allegory, synecdoche and chiasmus.